Feasibility of delivering integrated COPD-asthma care at primary and secondary level public healthcare facilities in Pakistan: a process evaluation. Issue 1 (2019) - Khan, Muhammad Amir; Khan, Muhammad Ahmar; Walley, John D; Khan, Nida; Sheikh, Faisal Imtiaz; Ali, Saima; Salahuddin, Ehsan; King, Rebecca; Khan, Shaheer Ellahi; Manzoor, Farooq; Khan, Haroon Jehangir
No abstract available